Biodiversitas Kumbang Koprofagus di Lahan Pertanian Organik dan Non-organik: Biodiversity of Coprophagous Beetles in Organic and Non- organic Farms - Hanna Latifa; Tri Atmowidi; Woro Noerdjito (Jurnal Sumberdaya Hayati, 2019)
Coprophagous beetle has important role in decomposition of organic materials. This research aimed to study and analyze the diversity and abundance of coprophagous beetles in organic and non-organic farms. Coprophagous beetles were collected in organic farm of Bina Sarana Bakti and non-organic farm of Seruni in Cisarua, West Java. In each location, twenty dung traps were set up in corn plants, carrot plants, cabbage plants, and onion plants. Totally, 15 species (610 individuals) of coprophagous beetles belonging to two families i.e Scarabaeidae and Aphodiidae were collected. Coprophagous beetles in organic farms (389 individuals, 13 species) more divers than that in non-organic farms (221 individuals, 10 species). There was no dominant species in both of locations (C<0.5). The most dominant species in organic farm was Copris reflexus (49%) and in non-organic farm was Onthopagus pauper (52%). Beetles similarity in organic and non-organic farm was 67%.